Inovasi Pendidikan Islam melalui Penerapan Design Thinking - Nurazis, Taufiq (STIT Fatahillah, 2025)
Educational innovation is an effort to continually improve and transform every aspect of life. To implement educational innovation, a specific strategy or method is required. One method for facing the challenges of sustainable education in the era of disruption is design thinking. The purpose of writing this article is to analyze the potential of the Design Thinking framework as an innovative solution in the management and development of the Islamic education curriculum. The method in this research uses a Qualitative method with a library research approach. Data were collected through the collection, selection, and critical extraction of reputable scientific journals, textbooks, and documents related to Design Thinking. The results of the study show that Design Thinking has several stages, including Empathy, Definition, Ideation, Prototyping, and Testing, in Islamic educational institutions to identify the authentic needs of students, teachers, and stakeholders, as well as designing innovative and effective solutions. Design Thinking offers a strategy that can improve the quality of learning, institutional governance, and relevance for graduates of Islamic educational institutions.